Alteration of Metabosensitive Afferent Response With Aging: Exercised versus Non-exercised Rats - Caron, Guillaume; Decherchi, Patrick; Marqueste, Tanguy (Frontiers in Aging Neuroscience, 2018)
This study was designed to evaluate the effect of aging on the activity of metabosensitive afferent fibers (thin muscle afferents from group III and IV) and to determine if physical activity performed at old age may influence the afferent discharge. Afferents from tibialis anterior and soleus muscles were recorded on non-exercised rats aged of 3, 6, 12, and 20 months and on animals aged of 12 and 20 months performing a daily incremental treadmill exercise protocol during the last 8 weeks preceding the recordings. Metabosensitive afferent fibers were activated with potassium chloride (KCl) and lactic acid (LA) injections into the blood stream or by muscle electrically-induced fatigue (EIF). Results indicated that aging is associated to a decrease in the magnitude of the responses to chemical injections and EIF. Unfortunately, physical activity did not allow restoring the metabosensitive afferents responses. These results indicate an alteration of the thin afferent fibers with aging and should be taken into account regarding the management of muscle fatigue and potential alterations of exercise pressor reflex (EPR) occurring with aging.